Cu AND Zn SUBSTITUTED HYDROXYAPATITE COATINGS ON TiO2 NANOTUBES FORMED BY ELECTROCHEMICAL METHODS - SUBHASMITA SWAIN; TAPASH RANJAN RAUTRAY (Innovare Journal of Engineering and Technology, 2016)
ABSTRACT Objective Hydroxyapatite (HA) coatings on TiO2 nanotubes (TNT) provide osteoconduction and hence promote bone healing and apposition, leading to the rapid biological fixation of implants. In the current study, TNT surfaces were formed by electrochemical anodization technique and Cu and Zn were simultaneously substituted in HA coating so as to form a coating with antibacterial properties with good osteoconductive surface. Methods: Ion substituted HA coatings such as Cu-HA and Zn-HA were deposited cathodically on TNT surfaces. This work elucidated the antibacterial effect and cytocompatibility of Cu and Zn substituted HA coating on TNT. To improve the antibacterial property of pure HA, Cu and Zn were substituted into its structure. Results: XRD of the coatings showed the formation of Cu-HA and Zn-HA while PIXE confirmed the coatings to be calcium deficient. MTT assay was employed to assess the cell survival rate of Cu-HA and Zn-HA coatings with osteoblast-like cells. Conclusion: While both the coating showed good bioactivity, better cell activities were observed in case of Zn-HA coating. Better cell activities on Zn-HA may be attributed to the cytocompatibility nature of Zn-HA and because of its higher roughness.